Island of shipwrecks - McMann, Lisa (McMann, Lisa. Unwanteds, 2015)
Alex and his friends from Artimé are stranded on a newly-discovered island, and they are not alone, while in Quill, his twin Aaron's power base grows as he joins with an unlikely ally in a risky plan to finally conquer Artimé.